Pengembangan Aplikasi Penanganan dan Pengurangan Sampah dalam Membantu TPS3R berbasis Android (Studi Kasus: TPS3R di Kota Batu) - Hilman Hamdani; Komang Candra Brata; Adam Hendra Brata (Fakultas Ilmu Komputer (FILKOM), Universitas Brawijaya, 2023)
Waste is one of the main problems faced by the Batu City Environmental Agency. One of the efforts of the Environmental Agency is to create the TPS3R program. Based on the results of a survey of 11 people who live near TPS3R, 8 of the 11 people are still not aware of the importance of sorting waste because it has become a habit of local residents to immediately dispose of waste without sorting it out. As many as 90% of the respondents felt interested if there was an application that could educate so that people could change their habits to always sort waste accompanied by awards in the form of points that can be exchanged into money if they have deposited it into TPS3R. In addition, TPS3R, which is currently active in Batu City, has internal problems regarding cash books that are not well recorded and lack of interest in TPS3R processed products. Therefore, a waste handling and reduction application was developed in helping the TPS3R problem in Batu City. Developed using the MVC-architecture kotlin programming language. Data storage for the entire app uses Firebase Realtime Database and designed its interface using Figma tools. In the development process, it uses the Prototype method. Application testing uses 4 factors, namely validation, compatibility, correctness and efficiency for TPS3R bookkeeping features and user satisfaction testing with the SUS method. In validation and compatibility tests get 100% valid results and successfully run on SDK versions from 24-32. Correctness testing gets 100% valid results by comparing manual and automatic calculations and up to 54% faster time efficiency when using the application. User satisfaction testing gets good predicate results for TPS3R managers and excellent for TPS3R users.